Strategi Humas Bawaslu Jabar dalam Pengawasan Siber Pemilihan Kepala Daerah - Hermawan, Herry (Jurnal Cyber PR, 2025)
This research is concerned with the communication strategy in Surveilans Siber in the regional election, in the context of a theory of social action. Based on the P-Process model, communication strategy consists of five levels, analysis, strategic design, development and testing, implementation, and evaluation. Through the qualitative research method, the analysis techniques in use was descriptive. Research shows that West Java's Bawaslu utilizes cyber monitoring and information campaigns to address election violations and boost public involvement. These initiatives are designed to shape community attitudes and behaviors regarding election supervision in the region. This maintenance process through the stages of analysis, strategic design, development and testing, implementation, and evaluation. Thus, this communication strategy other than a political activity as well as an arena of ideas and beliefs people have are systematically related to actual, spiritual and material conditions of existence. Based on the research findings, it is known that digital campaigns are increasing, yet cyber oversight regulations remain inadequate. Furthermore, the technological capacity and human resources (HR) for monitoring are still limited. Another factor is that public awareness regarding participation in cyber oversight and violation reporting remains low. Similarly, coordination between institutions and digital platforms has not yet been optimized.